2018
DOI: 10.3390/su11010059
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Impacts of Higher Education Institutions on Sustainable Development—An Analysis of Tools and Indicators

Abstract: Many higher education institutions (HEIs) have started to incorporate sustainable development (SD) into their system. A variety of sustainability assessment tools (SATs) have been developed to support HEIs to systematically measure, audit, benchmark, and communicate SD efforts. In recent years, stakeholders have increasingly asked HEIs to demonstrate their impacts on SD. These impacts are the direct and indirect effects an HEI has outside of its organizational boundaries on society, the natural environment, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
142
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 133 publications
(183 citation statements)
references
References 51 publications
6
142
0
2
Order By: Relevance
“…Much work has been done on the development of tools to assess sustainability specifically in HEIs, showing the importance of the theme. Several articles have reviewed these tools from different perspectives (e.g., [7,9,14,16,17,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]). However, it is observed that in these various reviews, the systematization is not homogeneous, noting a lack of common designations and objectives and including tools that do not have as main objective the assessment of the implementation of ESD or are not per se an assessment tool.…”
Section: Sustainability Assessment In Higher Educationmentioning
confidence: 99%
See 4 more Smart Citations
“…Much work has been done on the development of tools to assess sustainability specifically in HEIs, showing the importance of the theme. Several articles have reviewed these tools from different perspectives (e.g., [7,9,14,16,17,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]). However, it is observed that in these various reviews, the systematization is not homogeneous, noting a lack of common designations and objectives and including tools that do not have as main objective the assessment of the implementation of ESD or are not per se an assessment tool.…”
Section: Sustainability Assessment In Higher Educationmentioning
confidence: 99%
“…(i) assess only one of the dimensions of implementing sustainability in HEIs such as Campus operations (e.g., Campus Sustainability Assessment Framework-CSAF, [20]; National Wildlife Federation's State of the Campus, [34]) or Curricula (e.g., Sustainability Tool For Assessing Universities' Curricula Holistically, STAUNCH, [11]); (ii) evaluate only one pillar of sustainability, namely Environmental (e.g., Campus Ecology, [35], Environmental Performance Survey, [34]); (iii) only serve as manuals or supportive conceptual models (e.g., Greening Campuses, [36]); (iv) assess only the level of literacy and knowledge of population sustainability (e.g., SULITEST, [37]); (v) adapt by an Institution but based on other existing metrics (e.g., UNI-Metrics-Value Metrics and Policies for a Sustainable University Campus, [31]); (vi) specific to a type of HEI (e.g., Business School Impact System BSIS, see Reference [14]); (vii) serve only as guidelines for supporting communication of performance for sustainability but are not themselves an assessment tool. This is the case of the guidelines developed by the International Campus Sustainability Network and Global University Leader Forum [38], two international networks that suggest the organization of sustainability reports for HEIs, based on GRI indicators and the Sustainability Tracking tool, Assessment & Rating System-STARS [38].…”
Section: Sustainability Assessment In Higher Educationmentioning
confidence: 99%
See 3 more Smart Citations